2010
DOI: 10.1519/jsc.0b013e3181cbab96
|View full text |Cite
|
Sign up to set email alerts
|

Three Types of Kinematic Feedback and the Execution of the Hang Power Clean

Abstract: The type and quality of feedback provided during instruction influences motor skill learning. The purpose of the study is to gain a better understanding of how altering feedback can impact discrete dynamic movements that are integral to strength training programs. The effects of 3 types of feedback on the execution hang power clean (4 sets of 4 repetitions at 75% of 1 repetition maximum) were evaluated over 6 training sessions. Nine different movement indices of the hang power clean were assessed using Dartfis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 7 publications
4
43
0
3
Order By: Relevance
“…These findings are similar to those of Häkkinen et al [87], who indicated that snatch and clean and jerk technique failed after 4-6 repetitions. It is crucial to provide several forms of feedback in order to refine exercise technique for heavier repetitions in later phases [91,158]. Within the strength phase, it is recommended that high force movements are implemented in order to gain positional strength during weightlifting movements, as well as improve peak force production and RFD.…”
Section: Exercise Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to those of Häkkinen et al [87], who indicated that snatch and clean and jerk technique failed after 4-6 repetitions. It is crucial to provide several forms of feedback in order to refine exercise technique for heavier repetitions in later phases [91,158]. Within the strength phase, it is recommended that high force movements are implemented in order to gain positional strength during weightlifting movements, as well as improve peak force production and RFD.…”
Section: Exercise Selectionmentioning
confidence: 99%
“…Finally, the athletes must be coached appropriately during each weightlifting pulling derivative. As previously mentioned, proper exercise technique is vital; however, the practitioner must take a proactive role with their athletes in providing them with good demonstrations and various forms of feedback [91,158] in order for the athlete to become an expert with regard to exercise technique for the clean pull, snatch pull, hang high pull, jump shrug, and mid-thigh pull. In contrast, weightlifters may want to spend more time focusing on the catch phase, as optimal technique during this phase is an essential component of the sport.…”
Section: Conclusion and Practical Applicationsmentioning
confidence: 99%
“…One of augmented feedback, the Knowledge of Results (KR) was considered by many authors in 60's and 70's [14] and, more recently, in 80's [15], was deemed as one of the most important variables to control and acquire motor skills. Given the concerns acquired by the influence of KR on learning processes, it was even asserted that the more frequency, accuracy and immediacy when providing KR, the better learning rates would be reached.…”
Section: Augmented Feedback Reviewmentioning
confidence: 99%
“…The most prominent criticisms of past research on augmented feedback, along with the lack of separation of KR and KP, and the lack of retention or transfer tests, are about the use of "artificial" laboratory tasks and the lack of consideration of the characteristics of motor skills. It has been argued that the generalized principles of augmented feedback from the laboratory with one-dimensional tasks may not apply well to more complex real-world settings [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], and that skills with different characteristics need different types of feedback information for effective learning. The number of explanation for the lack of effectiveness on skill acquisition may be due to overly complex information presented, failure to provide critical feedback about the skill and not providing enough information for error detection [13].…”
Section: Introductionmentioning
confidence: 99%
“…34, 82 Thow, et al 34 reported significantly greater improvements in both initial and average velocity measurements in elite swimmers during the glide phase following a dive start when swimmers were provided with quantitative feedback to compliment the coach's instructions. Average velocity increased from 1.74±0.16 m•s -1 to 1.84±0.09 m•s -1 over a five week intervention period.…”
Section: Quantitative Technical Assessmentmentioning
confidence: 99%